Song Of The Spirit In The Jak Mania Chants: Tribute From Fans To Footballers - Sihombing, Lambok Hermanto; Aristia, Andhien Ayu; Bumi, Lanang Tirta (Universitas Negeri Semarang, 2021)
Chant is a supportive song that is usually shown to idols. Chants are performed by fans as a form of love and support for their idols. Chants usually contain words of encouragement and support and that make the enthusiastic in competition. This study aimed to analyze the chants from one of the Indonesian soccer teams, namely PERSIJA JAKARTA (Persatuan Sepak bola Indonesia Jakarta). The chants that the researchers used are Kesurupan, Majulah Persija, and Menerjang Badai. In order to help the researchers in doing the analysis, Fandom Theory is used in this study to elaborate the lyrics of those three chants. As the result, those three chants do not only contain words of encouragement but also moral messages and even critics towards government.